Limits of Application of the Institution of Free Credit by a Member of the Cooperative Savings and Credit Union - Skoczek, Jacek (PRAWO i WIĘŹ, 2024)
The author discusses the limits of the application of the institution of interest-free credit by members of the Cooperative Savings and Credit Union (SKOK). The concept of interest-free credit was introduced into Polish law as a result of the implementation of EU Directive 2008/48/EC, which allows member states to establish sanctions for breaches of national provisions adopted in accordance with this Directive.According to Polish law, a consumer may demand repayment of the credit without interest and other costs if the creditor has violated the information obligations specified in the Consumer Credit Act. Similar sanctions already existed in national law, but their wording was changed, including the requirement of a written declaration by the consumer.However, the interest-free loan sanction appears to be disproportionate and one-sided, negatively affecting the economic interests of the creditor. Its implementation is especially problematic in the case of SKOKs, where members have extended financial liability for the activities of the union.An analysis of the principle of proportionality in the context of the application of the interest-free credit sanction to SKOKs highlights the need to maintain a balance between consumer interests and the financial stability of the union. In the case of SKOKs, which operate on the basis of shared ownership by members and a common economic purpose, the application of the interest-free credit sanction requires particular caution and consideration of the specific nature of these relationships.The author of the article emphasizes the need to amend the regulations on interest-free credit in order to take into account the differences in the creditor’s misconduct and the specific economic relations between the creditor and the consumer. The de lege ferenda proposal suggests introducing differentiated sanctions and taking into account the actual damage to the consumer, which would allow for more proportionate and fair regulations regarding consumer protection and the stability of SKOK-type financial institutions.